Nationwide utilization of cardiopulmonary bypass in cardiothoracic trauma: A retrospective analysis of the National Trauma Data Bank. Issue 3 (September 2021) - Johnson, Benjamin P.; Hojman, Horacio M.; Mahoney, Eric J.; Detelich, Danielle; Karamchandani, Manish; Ricard, Caroline; Breeze, Janis L.; Bugaev, Nikolay
Abstract : BACKGROUND: The American College of Surgeons Committee on Trauma requires that all level I trauma centers have cardiopulmonary bypass (CPB) capabilities immediately available. Despite this mandate, there are limited data on the utilization and clinical outcomes among trauma patients requiring CPB in the management of injuries. The aim of this study was to evaluate the current use of CPB in the care of trauma patients. METHODS: This is a retrospective analysis of the National Trauma Data Bank from 2010 to 2015. Adult patients sustaining cardiothoracic injuries who underwent surgical repair within the first 24 hours of admission were included. Propensity score matching was used to compare outcomes (in-hospital mortality, hospital length of stay (LOS), intensive care unit LOS, and complications) between patients who underwent CPB within the first 24 hours of admission and those with similar injuries who did not receive CPB. RESULTS: A total of 28, 481 patients who met the inclusion criteria were identified, of whom 319 underwent CPB. Three-hundred three CPB patients were matched to 895 comparison patients who did not undergo CPB. Overall in-hospital mortality was 35%. Patients who were not treated with CPB had a significantly higher in-hospital mortality compared with those treated with CBP (odds ratio, 1.57; 95% confidence interval, 1.16–2.12; p = 0.003); however, complications were significantly lower in those who did not receive CPB (odds ratio, 0.63; 95% confidence interval, 0.47–0.86; p = 0.003). Hospital LOS (non-CPB: mean, 13.4 ± 16.3 days; CPB: mean, 14.7 ± 15.1 days; p = 0.23) and intensive care unit LOS (non-CPB: mean, 9.9 ± 10.7 days; CPB: mean, 10.1 ± 9.7 days; p = 0.08) did not differ significantly between groups. CONCLUSION: The use of CPB in the initial management of select cardiothoracic injuries is associated with a survival benefit. Further investigation is required to delineate which specific injuries would benefit the most from the use of CPB. LEVEL OF EVIDENCE: Therapeutic, level IV. Abstract : Supplemental digital content is available in the text.